LCOE Baseline for RME Surge WEC Device - Previsic, Mirko; Chertok, Allan; Staby, Bill; Ceberio, Olivier; Karthikeyan, Anantha (Marine and Hydrokinetic Data Repository (MHKDR); Re Vision Consulting, 2017)
This submission includes all the data to support an LCOE baseline assessment for the Resolute Marine Energy (RME) Surge WEC device